The Yara Gambirasio case: Collection strategy and mass screening used to find the perpetrator DNA in a difficult scenario. Issue 1 (December 2019) - Staiti, Nicola; Gentile, Fabiano; Pilli, Elena; Lago, Giampietro
Abstract: In the winter of 2011 a corpse of a teenager was found in a fallow field after three month of environmental exposure. The autopsy showed no sign of rape but the presence of several cuts on the victim's body. Despite exposure to weathering and animals, the clothes from the waist up were well preserved, whereas the trousers were extensively torn and the underpants were clearly cut. Searching evidence from the perpetrator was difficult since the traces present on the victim's clothes and underpants were subjected to morphological and chromatic modifications due to the environmental exposure. Initially, sample collection was based on an integrated approach that involved circumstantial information and inspection with the forensic light. The use of this light source allowed us to identify some areas with more clearly fluorescence, also visible to the naked eye, that were the first to be collected. The accurate inspection led us to perform approximately 300 samplings on the clothes. In one of these areas (called 31-2) located on the underpants, the results of the sampling showed the presence of alleles unrelated to the victim. As a result, an extensive sampling through the application of a virtual grid was undertaken in this area to confirm and improve the male profile and obtain serological information. Due to the complete absence of other relevant clues on the perpetrator, when a full male profile -Unknown Male # 1 (UM#1)- was found on the victim's clothes, a huge mass screening that involved the collection and analysis of over 16, 000 reference samples was carried out, until a full match was obtain.